Glucose- regulated protein 78 (GRP78) in renal cell carcinoma: A novel biomarker for predicting tumor behavior. Issue 6 (June 2021) - Kumar, Manoj; Garg, Harshit; Gupta, Nidhi; Sharma, Alpana; Kaushal, Seema; Kumar, Rajeev; Dinda, Amit Kumar
Abstract: Objective: To study the mRNA and protein expression of GRP78 in tumor and serum of the RCC patients and compare with the controls and to correlate the expression with the grade and stage of RCC. Materials and methods: A prospective cohort study involving 60 patients planned for radical/partial nephrectomy for primary RCC between July 2017 to June 2019. The RCC and adjacent non-tumorous renal tissues (Control) along with serum samples of patients were collected. Control for the serum samples is from the patients undergoing simple nephrectomy for non-functioning kidney due to benign etiology. The GRP78 expression was studied using RT-PCR for mRNA expression, Western blot analysis and immunohistochemistry (IHC) for protein expression and using ELISA in serum for both the subjects and controls. Results: Mean age of patients was 50.3 years. The mRNA and protein expression of GRP78 in tissue samples were significantly higher in RCC patients as compared to controls (p < 0.001). IHC also demonstrated significantly higher expression in tumour samples as compared to controls (p < 0.001). Circulatory levels of GRP78 in serum samples were also significantly increased (p < 0.0001) in RCC patients in comparison to control subjects. The expression of GRP78 in circulation significantly correlated with the pathological tumor stage (p = 0.03), grade of disease (p < 0.001). Conclusion: The GRP78 in RCC is significantly upregulated both at molecular and protein level expression. The overexpression of GRP78 correlates with the stage and grade of disease, thereby, highlighting its prognostic ability. Abstract : RCC; Glucose regulated protein 78; Endoplasmic reticulum chaperone protein; Binding immunoglobulin protein (BiP).